The Effect of Students’ Learning Models and Style on Students’ Achievement in Reading - Elisa P.N. Nainggolan; Busmin Gurning; Sumarsih Sumarsih (Universitas Negeri Medan, 2014)
The objectives of the research were to find out whether a) students’ achievement in reading comprehension taught by using Jigsaw model was higher than taught by using Task-Based Learning (TBL) b) students’ achievement in reading comprehension with visual style was higher than that students with auditory style. The population was the students of SMA Budi Murni 2 Medan with 104 students. The samples were 3 parallel classes and two classes by applying cluster random sampling. The questionnaire was administered for classifying the students upon the visual and auditory learning style. The data were analyzed by applying two-way analysis of variance (ANOVA) at the level of significance α= 0.05. The result proved that students’ achievement in reading comprehension taught by using Jigsaw was higher than that taught by using TBL, students’ achievement in reading comprehension with visual learning style was higher than those with auditory learning style and there was interaction between models of learning and learning styles on students’ achievement in reading comprehension. Moreover, Tuckey-test result also showed that visual style students got higher achievement if they were taught by using Jigsaw model while auditory style students got higher achievement if they were taught by using TBL model. Keywords: Effect; Models of Learning; Reading Comprehension; Students’ Learning Style; Students’ Achievement